The role of the combined use of experimental and computational methods in revealing the differences between the micron-size particle deposition patterns in healthy and asthmatic subjects - Farkas, Árpád; Lizal, Frantisek; Jedelsky, Jan; Elcner, Jakub; Karas, Jakub; Belka, Miloslav; Misik, Ondrej; Jicha, Miroslav (Journal of aerosol science, 2020)
Quantification of airway deposition of aerosol particles is essential for the assessment of health risks of detrimental particles. Knowledge of deposition distribution is important also in the case of treatment with aerosolised drugs. It is also worth considering that deposition of inhaled particles in severe asthmatics can be different from the deposition in healthy subjects due to the modified breathing parameters, airway geometry and lobar flow distribution. The aim of this study was to apply combined experimental and numerical techniques to quantify the upper airway and bronchial deposition of the inhaled microparticles in healthy individuals in comparison with asthma patients. Idealised and realistic physical and digital replicas of the human airways were constructed. Deposition fractions and efficiencies of inhaled polydisperse mannitol and chitosan particles in different airway sections were measured and calculated. Deposition fraction of polydisperse mannitol particles in the idealised airway geometry assuming breathing conditions of healthy subjects was 21.9% and 18.3% when determined experimentally and by numerical simulations, respectively. Experimental measurements of deposition fraction of chitosan particles in the same geometry, but assuming breathing parameters characteristic of severe asthmatics yielded 32%, while simulations provided 30.1% for the same conditions. Extrathoracic deposition fraction of mannitol particles in healthy subjects measured in the realistic geometry was 71.1%, while bronchial deposition fraction was 5.3%. The corresponding simulations yielded 76.2% and 8.9% deposition fractions in the upper and bronchial airways, respectively. There was a good agreement between the experimental and simulation deposition results also in the different predefined sections of the airways. Present pilot study proved that lobar flow redistribution due to severe asthma significantly modified the deposition distribution of micro-particles. Although the present results refer only to small groups of healthy and asthmatic individuals, it clearly demonstrates the capability of carefully validated models to simulate the deposition of micron-size particles in larger populations of both groups. •Deposition distribution of micro-particles in idealised and realistic upper and central airways was measured and simulated.•Deposition distribution of micro-particles in idealised and realistic upper and central airways was measured and simulated.•Good agreement of numerical and experimental data was found.•The modified breathing of asthmatics significantly changed the deposition distribution of micro-particles.•Combination of numerical and experimental techniques can be a powerful tool of the quantification of particle deposition.